Peran Manajemen Kelas Terhadap Keaktifan Belajar Siswa di MA DDI Maspul Kabupaten Bone - Gita Sufitri; Fajri Dwiyama; Bachtiar Aziz (Institusi Agama Islam Negeri (IAIN) Bone, 2025)
This study discusses the role of classroom management on student learning activity. The purpose of this study is: to find out the role of classroom management in MA DDI Maspul, to find out the learning activity of students at MA DDI Maspul and the role of classroom management on student learning activity at MA DDI Maspul. The author uses qualitative research methods (Qualitative Research) through a management and sociological approach, the data collection techniques used are interviews, observations and documentation taken from primary and secondary data sources. The data analysis techniques used are data reduction, data presentation and conclusion drawing as well as data verification. The results of the study show that 1) The role of classroom management in MA DDI Maspul has been running as it should, starting from class planning, classroom management, classroom leadership and classroom control. 2) the student's learning activity at MA DDI Maspul has weaknesses in terms of visual activities, oral activities, and listening activities. 3) The role of classroom management in student learning activity at MA DDI Maspul is seen from the classroom management in terms of planning, organizing, leadership and control has a role in activeness.